The Relationship Between Shift Work and Body Mass Index Among Canadian Nurses - Smith, P.; Fritschi, Lin; Reid, Alison; Mustard, C. (Elsevier Science, 2013)
Aim: The aim of this study was to examine the relationship between shift schedule and body massindex (BMI) among a sample of Canadian Nurses.Background: Higher BMI values have been reported for employees working non-standard shiftscompared to those working a regular daytime schedule. Little is known about the pathways throughwhich shift work is associated with higher BMI.Methods: This study was a secondary analysis of a sample from National Survey on the Work andHealth of Nurses (N=9291).Results: We found a small, but statistically significant, difference in BMI scores across shiftschedule categories with higher BMI scores reported among female nurses working night or mixedshift schedules, compared with those working a regular daytime schedule. Adjustment for workingconditions and employer supported facilities did not attenuate the association between shift work andBMI scores.Conclusions: The potential public health importance of this relationship requires furtherinvestigation given the small, but statistically significant, differences observed in this sample.